Indigenous and mestizos sense of community from San Cristóbal de las Casas (Chiapas, México). An empirical study. - Esteban Guitart, Moisès; Sánchez Vidal, Alipio (Anales de Psicología / Annals of Psychology, 2012)
This study explores cross-cultural viability of a 18 item self-report scale of sense of community developed and trested in European contexts. A questionnaire designed to evaluate Sense of Community was administered to 151 indigenous and 166 mestizos from San Cristóbal de las Casas (Chiapas, México), a population which has never been studied before. Results showed San Cristóbal de las Casas is communitarian in both groups. Statistical analysis showed the scale to be reliable and multidimensional although dominated by a main relational factor, “neighborhood interaction”, with two other, minor although conceptually meaningful ones: “territorial rooting” and “interdependence”. Results supported most of Sarason’s theory and of past empirical and theoretical analyses.